Common Data Elements, Scalable Data Management Infrastructure, and Analytics Workflows for Large-Scale Neuroimaging Studies - Kuplicki, Rayus; Touthang, James; Al Zoubi, Obada; Mayeli, Ahmad; Misaki, Masaya; , NeuroMAP-Investigators; Aupperle, Robin L.; Teague, T. Kent; McKinney, Brett A.; Paulus, Martin P.; Bodurka, Jerzy (Frontiers in Psychiatry, 2021)
Neuroscience studies require considerable bioinformatic support and expertise. Numerous high-dimensional and multimodal datasets must be preprocessed and integrated to create robust and reproducible analysis pipelines. We describe a common data elements and scalable data management infrastructure that allows multiple analytics workflows to facilitate preprocessing, analysis and sharing of large-scale multi-level data. The process uses the Brain Imaging Data Structure (BIDS) format and supports MRI, fMRI, EEG, clinical and laboratory data. The infrastructure provides support for other datasets such as Fitbit and flexibility for developers to customize the integration of new types of data. Exemplar results from 200+ participants and 11 different pipelines demonstrate the utility of the infrastructure.